2022
DOI: 10.3389/fonc.2022.922016
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Metastasis of Primary Lung Cancer: Case Report and Systematic Review With Pooled Analysis

Abstract: BackgroundGastric metastasis from lung cancer (GMLC) is a rare occurrence. The clinicopathological characteristics, outcomes, and prognostic factors remain largely elusive.MethodsWe conducted a systematic review on case reports and case series of GMLC by scanning MEDLINE, Embase, and ISI Web of Knowledge. Data involving the clinicopathological features, treatment, and outcomes were extracted and analyzed. Survival analysis was performed using Kaplan–Meier method. The Cox proportional hazards regression model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…First, what is the pathway through which lung cancer metastasizes to the stomach? Although gastric metastasis from lung cancer is rare, it can spread to the gastrointestinal tract through hematogenous and lymphatic routes[ 13 ]. Based on the findings in the positive LN, which was consistent with those in the stomach lesions, we believe that this patient’s gastric metastasis was through the lymphatic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…First, what is the pathway through which lung cancer metastasizes to the stomach? Although gastric metastasis from lung cancer is rare, it can spread to the gastrointestinal tract through hematogenous and lymphatic routes[ 13 ]. Based on the findings in the positive LN, which was consistent with those in the stomach lesions, we believe that this patient’s gastric metastasis was through the lymphatic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric metastasis is uncommon for lung cancer in the clinic. Metastatic lesions may develop at any site of the stomach, mainly locating in the middle and upper thirds ( 11 , 12 ), and solitary gastric metastases are more common than multiple metastases ( 13 ). The endoscopic manifestations of gastric metastases may be diverse and the most common endoscopic appearance is submucosal mass with or without ulceration, and the ulceration at the apex of the submucosal mass usually be described as volcano-like or umbilicated ( 7 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study further reported the characteristics of small gastric metastases under BLI-ME; the microvascular and microsurface patterns of the covering mucosa may be regular or irregular, and the demarcation line between lesion and normal mucosa may exist or not correspond to the development stage of metastases; however, in the present study, certain common characteristics between the two cases were found under BLI-ME, such as an obviously widened IP and extended SECN, indicating that lesions developed beneath the superficial epithelium. These above endoscopic characteristics may be explained by the growth pattern of metastasis from a distant primary cancer; cancerous cells traveling through the blood or lymph system usually disseminate into the gastric submucosal layer first and then develop as a submucosal lesion ( 12 , 16 ), with further growth it may break through the covered epithelium and present as a central defection of the mucosa, or even erosion and ulcer. Endoscopic ultrasonography (EUS) has been widely used in the diagnosis and management of gastrointestinal neoplasms, particularly in gastric subepithelial lesions due to its excellent capability in evaluating the originating layer, echo level and internal echo pattern ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations